The export potential of Uzbekistan with the use of innovative analytical tools - Sultanova L. SH, Adilov. B. B,Halmirzaev A. A.,Bekmuradov N. H. (International Journal of Advanced Science and Technology, 2020)
This article investigates major points of the export potential of Uzbekistan with the use of innovative analytical tools. In this article, research pinpoints feature of the methodology and theoretical points of the Uzbekistan with the use of innovative analytical tools. In conclusion, it makes outcomes and shortcomings of the issue export potential of Uzbekistan with the use of innovative analytical tools.